Stereotypy i uprzedzenia w twórczości Anny Lauermannovej-Mikschovej = Stereotypes and prejudice in Anna Lauermannová-Mikschová`s work - Kubanová, Kateřina (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Anna Lauermannová-Mikschová, writer and founder of the first literary salon in Czech countries, published the majority of her titles under pen name Felix Téver: Šťastný u břehů Tibery (Happy at the Banks of the Tiber River). Her work features a wide range of genres from short stories, novels, plays to sketches, reflections and, last but not least, memoires (memories, journals), the latter being probably the best demonstration of her narrative and observative skills. Reflecting her personal experience and thoughts, her work also pointed to a wide palette of issues that have not lost their topicality until present days, such as relationship between woman and man, role of women in society, stereotypes, prejudice.
Keywords: Téver, Felix (właśc. Lauermannová-Mikschová, Anna; 1852-1932); czeski pisarz; płeć; recepcja; interpretacja; stereotypy; Czech female writer; gender; reception; interpretation; stereotypes